Dampak Penggunaan Fitur Whatsapp Sekali Lihat terhadap Keefektifan Komunikasi - Renny Soelistiyowati; Geraldo Armayudha; Harries Maritasari; Risa Prayudhi; Adi Nurhadi (Jurnal Penelitian Sosial Ilmu Komunikasi, 2025)
Advancements in digital communication have introduced features like WhatsApp's 'View Once', which allows images or videos to be viewed a single time before deletion. While designed to enhance user privacy, this feature may affect communication effectiveness, particularly in message clarity and information retention. This study explores the impact of the 'View Once' feature on communication among students of the Digital Communication and Media Study Program, SV IPB University. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation involving students who frequently use this feature in both personal and academic settings. Findings indicate that while 'View Once' helps maintain privacy and limits the spread of sensitive content, it also presents drawbacks. These include unclear messaging, inconsistent communication, a lack of awareness of the recipient’s background and cognitive processing, technical errors, and reduced empathy. Furthermore, the feature often necessitates redundancy to ensure message comprehension, making it less suitable for communications requiring depth or future reference. The study concludes that although 'View Once' offers privacy benefits, its application should align with communication goals to avoid impairing message delivery. Users are advised to carefully consider the context and urgency of the message before opting for this feature, especially in situations demanding clarity and repeat access.